2008
DOI: 10.1111/j.1524-4741.2008.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

MRI and1H MRS of The Breast: Presence of a Choline Peak as Malignancy Marker is Related to k21 Value of the Tumor in Patients with Invasive Ductal Carcinoma

Abstract: To assess which specific morphologic features, enhancement patterns, or pharmacokinetic parameters on breast Magnetic Resonance Imaging (MRI) could predict a false-negative outcome of Proton MR Spectroscopy ( 1 H MRS) exam in patients with invasive breast cancer. Sixteen patients with invasive ductal carcinoma of the breast were prospec-tively included and underwent both, contrast-enhanced breast MRI and 1 H MRS examination of the breast. The MR images were reviewed and the lesions morphologic features, enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Another study by Baek et al reported that the choline level was found to be significantly higher in lesions presenting as mass type compared to non-mass type diffuse enhancements, and a significant correlation was found between the choline level and pharmacokinetic parameter indicating that tissues with a high choline level have higher wash-out rates in DCE-MRI (17). Our pilot findings from a total of 18 subjects and 24 lesions needs to be treated with caution since another recent study by Geraghty et al reported that choline was detectable only 14 out of 16 cancer subjects resulting in a false negative choline level in two breast cancer subjects (18).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Another study by Baek et al reported that the choline level was found to be significantly higher in lesions presenting as mass type compared to non-mass type diffuse enhancements, and a significant correlation was found between the choline level and pharmacokinetic parameter indicating that tissues with a high choline level have higher wash-out rates in DCE-MRI (17). Our pilot findings from a total of 18 subjects and 24 lesions needs to be treated with caution since another recent study by Geraghty et al reported that choline was detectable only 14 out of 16 cancer subjects resulting in a false negative choline level in two breast cancer subjects (18).…”
Section: Discussionmentioning
confidence: 43%
“…Similarly, the choline groups contain methylene protons that give rise to J-coupled multiplets in the 3-4 ppm region as described above. Due to significant overlap of these J-coupled multiplets, it is difficult to reliably assign these peaks using 1D MRS. MR spectral editing techniques based on subtraction to unravel the overlapping resonances are limited in use because they rely on J-coupled protons that have well separated multiplets and are limited to selection of one metabolite per measurement (18)(19)(20)(21). Single-shot based multiple-quantum filtered MR spectroscopic sequences have also been implemented on whole body scanners, but signal losses associated with various coherence transfer pathways make it less attractive for human applications (22,23).…”
mentioning
confidence: 98%
“…There have been single-voxel MR spectroscopic studies proposing quantifimeasurements were previously used for the detection of Cho (ie, detectability or Cho signal-to-noise ratio) (22)(23)(24)(25)27,28 ). In our study, a recently published multivoxel MR spectroscopic method based on quantitative measurement was implemented ( 26 ).…”
Section: Multivoxel Mr Spectroscopymentioning
confidence: 99%
“…The single-voxel technique has limitations in terms of lesion coverage, which may affect the sensitivity of the assessment of Cho from just one voxel in view of tumor heterogeneity ( 22,26 ). Multivoxel MR spectroscopy, referred to as spectroscopic imaging or chemical shift imaging, acquires spectroscopic information from a large volume of interest subdivided into an array of voxels measured in a single measurement (22)(23)(24)(25)(26)(27)(28). Therefore, the multivoxel MR spectroscopic technique is suitable for analyzing the regional distribution of tumor metabolites and studying tissue heterogeneity.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation